Спектральний метод для дослідження взаємодії електромагнітного поля в системі металева наначастка - речовина в задачах контролю навколишнього природного середовища - Ілляшенко, Л. М. (ХНУРЕ, 2020)
The given work is devoted to the modern developments in the field of nanodevice design for environmental quality control, the principle of working for those is based on the use of plasmon resonances of noble metal nanoparticles, sensitive to any change in external environment. The dependence of resonating wavelength on various parameters is possible to be found. This permits adjusting the shape and size of nanoparticle in the most beneficial way to make it possible to build novel nanodevices covering a wide range of desired properties. The set of mathematical procedures demonstrates performances of developed algorithm, that allows solving a lot of new challenging problems